THE STRATEGY IN RETAINING GENERATION Z EMPLOYEES OF PT. BANK RAKYAT INDONESIA (PERSERO) TBK, BRANCH MANADO - Nurul Winarno; Paulus Kindangen; Maria V. J. Tielung (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
Generation Z, the newest in the workplace shows different characteristics from the previous generation. Where, there is still lack of information regarding to retain Generation Z, makes it difficult to determining the most effective retention strategy for this generation. This study aims to analyze the retention strategy used by PT. Bank Rakyat Indonesia (Persero) Tbk, Branch Manado in retaining Generation Z employees in the workplace, assessed based on the company low turnover rate indicating the success of the strategy and retention practices implemented. This study used a qualitative method with a purposive sampling technique. This sample uses 3 Management and 5 Generation Z employees as the informants. Data collection was carried out by using in-depth interviews, observation, documentation and secondary data or triangulation were also conducted and act as validity test to complete this study. From the findings, there are 5 strategies used, such as: 1). Organizational Culture, 2). Technology Digital 3). Employer Branding, 4). Development, 5). Remuneration & Benefits as strategies and practices used to retain Generation Z employees in the workplace. The results obtained show that all succeed in motivating and determining Generation Z employees’ decision to retain at PT. Bank Rakyat Indonesia (Persero) Tbk, Branch Manado.   Keywords: human resource management, strategy in retaining generation z employees